Impact of the African monsoon variations on silicate chemical weathering in the Nile basin - (:unkn) unknown (My University, 2017)
This thesis presents a reconstruction of the chemical weathering in the Nile basin since 100.000 years. His objective is to better understand the impact of climatic variations on chemical weathering, to better. This work is based on the geochemistry study on marine core recorded in the Nile delta, on a time scale of 100.000 years. It use a novel approach with the coupling of à source tracer (εNd) and chemical weathering tracers (δ7Li and elementary ratios) on the fine fraction (< 2µm). In addition, it was analyzed samples of each actual Nil sources and a core sample from Tana Lack (Ethiopie). The results of this studies have enabled to reconstruct the chemical weathering variations in the Nile basin since 100.000 years. It show a rapid respond of chemical weathering to climate variations. This was also observed by important impact of North Atlantic climate variations on the decrease of chemical weathering in the Nile basin. At present, the chemical weathering flux and the CO2 consumption of the Ethiopian traps are low comparted to the other basaltic regions, as the Deccan. However, our results show that during the most humid periods (African Humid Period) the CO2 consumption was 2 to 3 time higher than today. This indicates that the Ethiopian traps could be have played a non-negligible role in the global CO2 cycle during the Cenozoic, and principally during the most humid periods in North Africa. Finally, analytical developments have been realized to be able to exploit the lithium isotopes on biogenic carbonates as a new tracer of Nile water flood. The results suggest an influence of “vital” effect and diagenetic process.
Keywords: African Research